Recessive Inheritance of Congenital Hydrocephalus With Other Structural Brain Abnormalities Caused by Compound Heterozygous Mutations in ATP1A3 - Allocco, August A.; Jin, Sheng Chih; Duy, Phan Q.; Furey, Charuta G.; Zeng, Xue; Dong, Weilai; Nelson-Williams, Carol; Karimy, Jason K.; DeSpenza, Tyrone; Hao, Le T.; Reeves, Benjamin; Haider, Shozeb; et al. (Frontiers in Cellular Neuroscience, 2019)
Background: ATP1A3 encodes the a3 subunit of the Na+/K+ ATPase, a fundamental ion-transporting enzyme. Primarily expressed in neurons, ATP1A3 is mutated in several autosomal dominant neurological diseases. To our knowledge, damaging recessive genotypes in ATP1A3 have never been associated with any human disease. Atp1a3 deficiency in zebrafish results in hydrocephalus; however, no known association exists between ATP1A3 and human congenital hydrocephalus (CH). Methods: We utilized whole-exome sequencing, bioinformatics, and computational modeling to identify and characterize novel ATP1A3 mutations in a patient with CH. We performed immunohistochemical studies using mouse embryonic brain tissues to characterize Atp1a3 expression during brain development. Results: We identified two germline mutations in ATP1A3 (p. Arg19Cys and p.Arg463Cys), each of which was inherited from one of the patient’s unaffected parents, in a single patient with severe obstructive CH due to aqueductal stenosis, along with open schizencephaly, type 1 Chiari malformation, and dysgenesis of the corpus callosum. Both mutations are predicted to be highly deleterious and impair protein stability. Immunohistochemical studies demonstrate robust Atp1a3 expression in neural stem cells, differentiated neurons, and choroid plexus of the mouse embryonic brain. Conclusion: These data provide the first evidence of a recessive human phenotype associated with mutations in ATP1A3, and implicate impaired Na+/K+ ATPase function in the pathogenesis of CH.